Identifying Nurse and Patient Satisfaction with Handover Implementation - Alkanda, Wahid Hasyim; Rachmawaty, Rini; Irwan, Andi Masyitha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to assess nurse and patient satisfaction with how handoffs are handled. The methodology used is literature review. The Cochrane, PubMed, Ebsco, and Garuda Libraries are included in the Cochrane, PubMed, Ebsco, and Garuda Libraries. Each article discusses how surrender techniques affect nurse and patient satisfaction. Patients and nurses can benefit from different types of handover between shifts, rooms, and units, handover between nurses and nursing students, and SBAR (situation, background, assessment, and recommendations) communication techniques. Handover implementation can have a positive impact on patients and nurses, increase the knowledge of nurses and patients, and reduce malpractice cases.Keywords: Handover, Nurse Satisfaction, Patient Satisfaction